1074. Surveillance of SARS-CoV-2 variants of concern (VOC) in hospital wastewater (WW) and its correlation with hospitalized cases of COVID-19 and the occurrence of outbreaks. (15th December 2022) - Acosta, Nicole; Chavarriaga, Maria Bautista; Waddell, Barbara Jean M; McCalder, Janine; Du, Kristine; Pradhan, Puja; Sedaghat, Navid; Papparis, Chloe; Chen, Jianwei; Doorn, Jennifer Van; Xiang, Kevin; Chan, Leslie; et al.
Abstract: Background: WW surveillance enables real time monitoring of SARS-CoV-2 burden in defined sewer catchment areas. Here, we assessed the occurrence of total, Delta and Omicron SARS-CoV-2 RNA in sewage from three tertiary-care hospitals in Calgary, Canada. Methods: Nucleic acid was extracted from hospital (H) WW using the 4S-silica column method. H-1 and H-2 were assessed via a single autosampler whereas H-3 required three separate monitoring devices (a-c). SARS-CoV-2 RNA was quantified using two RT-qPCR approaches targeting the nucleocapsid gene; N1 and N200 assays, and the R203K/G204R and R203M mutations. Assays were positive if Cq< 40. Cross-correlation function analyses (CCF) was performed to determine the time-lagged relationships between WW signal and clinical cases. SARS-CoV-2 RNA abundance was compared to total hospitalized cases, nosocomial-acquired cases, and outbreaks. Statistical analyses were conducted using R. Results: Ninety-six percent (188/196) of WW samples collected between Aug/21-Jan/22 were positive for SARS-CoV-2. Omicron rapidly supplanted Delta by mid-December and this correlated with lack of Delta-associated H-transmissions during a period of frequent outbreaks. The CCF analysis showed a positive autocorrelation between the RNA concentration and total cases, where the most dominant cross correlations occurred between -3 and 0 lags (weeks) (Cross-correlation values: 0.75, 0.579, 0.608, 0.528 and 0.746 for H-1, H-2, H-3a, H-3b and H-3c; respectively). VOC-specific assessments showed this positive association only to hold true for Omicron across all hospitals (cross-correlation occurred at lags -2 and 0, CFF value range between 0.648 -0.984). We observed a significant difference in median copies/ml SARS-CoV-2 N-1 between outbreak-free periods vs outbreaks for H-1 (46 [IQR: 11-150] vs 742 [IQR: 162-1176], P< 0.0001), H-2 (24 [IQR: 6-167] vs 214 [IQR: 57-560], P=0.009) and H-3c (2.32 [IQR: 0-19] vs 129 [IQR: 14-274], P=0.001). Conclusion: WW surveillance is a powerful tool for early detection and monitoring of circulating SARS-CoV-2 VOCs. Total SARS-CoV-2 and VOC-specific WW signal correlated with hospitalized prevalent cases of COVID-19 and outbreak occurrence. Disclosures: All Authors : No reported disclosures.